Management of patients with acute promyelocytic leukemia - Kayser, Sabine; Schlenk, Richard Friedrich; Platzbecker, Uwe (Leukemia, 2018)
With the introduction of all-trans retinoic acid (ATRA) and arsenic trioxide (ATO) acute promyelocytic leukemia (APL) has become from a detrimental to one of the most curable malignant diseases in humans. In particular, the chemotherapy-free regimen with ATO/ATRA has been proven to be highly effective in de novo APL and has become standard first-line therapy in younger adult, non-high-risk patients. Nevertheless, early death is still a major issue in APL, particularly in older patients, emphasizing the need of rapid diagnostics and supportive care together with immediate access to ATRA-based therapy. Despite the dramatic progress achieved in therapy of APL challenging situations occur, particularly in patients excluded from controlled studies with clinical knowledge mainly based on case reports and registries. Rapid identification and treatment of newly diagnosed patients as well as the management of toxicities and complications remain challenging. We offer up-to-date information and guidance regarding treatment of APL. Based on a literature review of existing scientific evidence we also discuss the approach to high-risk, elderly, pregnant and pediatric patients, treatment in patients with renal failure as well as of therapy-related or relapsed/refractory APL.
Gesehen am 10.12.2019